Impact of the Ngäbe Indigenous People Mobility between Panamá and Costa Rica on their Culture and Lifestyle - Peñuelas Peñarroya , Anna (2025)
This article analyzes the impact of the temporary mobility of the Ngäbe indigenous people from their communities of origin in the Ngäbe-Buglé Comarca, Panama, to the agricultural areas of Costa Rica, to work in the coffee harvest. Based on the experiences of different Ngäbe families collected in a multi-sited ethnographic fieldwork, carried out both at origin and destination, this text reflects on the consequences of this annual journey to the neighboring country, not only in their economy and lifestyle but also in their social relationships and in their political, social and gender vision, thus opening the door to new realities and potential transformations in their traditional practices.